Implementation of The Corporate Social Responsibility Program of PT. Adaro Indonesia as a Community Empowerment Effort - Yulinda Erlistyarini (Institute of Computer Science (IOCS), 2022)
The Corporate Social Responsibility (CSR) program in its implementation is difficult to separate from community empowerment. Referring back to the purpose of carrying out this corporate social responsibility program, namely to create an empowered community, especially the people who live within the company's own environment. CSR as an effort to handle the impact of company development is a reflection of the company's concern for the impact of social, economic and environmental conditions in the vicinity. This research is to see how the implementation of Corporate Social Responsibility (CSR) programs conducted by PT. Adaro Indonesia, which has administrative operational areas located in Tabalong Regency and Balangan Regency, South Kalimantan Province, can contribute to community empowerment in several villages in the area around the company which are divided regionally. Purposive sampling technique was used in determining the informants according to the existing criteria, namely those who were directly involved in the process of implementing the CSR program of PT. Adaro Indonesia. The realization of the Corporate Social Responsibility program of PT. Adaro Indonesia, namely “Adaro Turns On Change, which targets several sectors, namely education, the environment, and the economy.